2021
DOI: 10.55279/jafmdc.v2i2.102
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Plantar Fasciitis among Females in Teaching Profession

Abstract: Objective: To find the frequency of plantar fasciitis among females teachers in Sialkot and to explore the relationship of heel pain due to plantar fasciitis with age, body mass index (BMI), type of shoes wearing and standing hours.Methodology: This cross-sectional study was the project of Sialkot College of physiotherapy (SCPT). It was conducted in February to March 2018 after taking ethical approval from institutional review board of SCPT (IRB-SCPT DPT-115-2018). Sample size was 150 subjects. Female teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In summary, while our study found no significant prevalence of plantar fasciitis among nurses based on the scoring scale, there was a notable association with the use of high-heeled shoes, indicating a potential risk factor. These findings underscore the importance of ergonomic considerations in nursing footwear to mitigate the risk of plantar fasciitis and enhance the overall well-being of nursing professionals (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In summary, while our study found no significant prevalence of plantar fasciitis among nurses based on the scoring scale, there was a notable association with the use of high-heeled shoes, indicating a potential risk factor. These findings underscore the importance of ergonomic considerations in nursing footwear to mitigate the risk of plantar fasciitis and enhance the overall well-being of nursing professionals (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 83%
“…The plantar fascia plays a crucial role in protecting the medial arch and providing tensile strength to the metatarsal bones. Plantar fasciitis typically results from inflammation at the origin of the medial calcaneal tuberosity due to repetitive stress, leading to a degenerative condition affecting the plantar fascia (1). The condition is known to impact both active and sedentary individuals (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no significant relation between BMI, standing hours and Plantar fasciitis. Physical activities were affected by the condition 21 . Limitations: This study was not applicable worldwide because data collection was done in selected hospitals of Lahore, so there can be information assortment inclination.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical findings include plantar and medial heel pain, mainly with initial steps after a period of inactivity and following prolonged weight bearing 1. Lifetime prevalence estimates are up to 34.7% in the general population 3–6. Most of the time, PF is self-limiting, but the time for complete resolution of symptoms can take up to 1 year, disabling patients’ quality of life 7.…”
Section: Introductionmentioning
confidence: 99%